The primary teacher development project = (The World Bank in Vietnam (WB), 2003)
The objective of the Primary Teacher Development Project for Vietnam is to lay the foundation for a nationwide program to upgrade the quality of the primary teaching service. The project has four main components. The first develops teacher professional standards (profile) by supporting a Profile Coordination Team, applies the profile to training courses and to teacher assessment, and finances action research to refine the profile. The second component funds a training program for teachers and education managers. It specifically finances a needs assessment and specification of the contents of the training packages and preparation of trial training packages, improves the capacity of teacher training institutes, supports the appraisal of training packages, and publishes and delivers training modules. The third component provides suppots for a Quality Assurance Team, improves the personnel management information system, develops accreditation and teacher classification procedures, and provides communications and training for school improvement. The fourth component supports revision in the Terms of Service for teachers. It supports technical assistance and research, preparation and discussion of options and supporting changes, and consensus building activities.